MOTIVASI WISATAWAN BERBAGI PENGALAMAN WISATA MELALUI INSTAGRAM - Firdausy Hakim, Mutiara; Suardana, I Wayan; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 2 (2019): Jurnal IPTA (December 2019)DO - 10.24843/IPTA.2019.v07.i02.p10, 2019)
There are many photo posts or videos uploaded by tourists at Padang-Padang beach and make it an interesting phenomenon because travelers have shared their tourism experience to social media. The research aims to find out the motivation of tourists to share that travel experience. Respondents in this study amounted to 190 respondents, sample selection using the Purposive sampling method, data in the research was analyzed using factor analysis assisted by the SPSS statistical version 17.0 for Windows. The results of this study are: 1) the motivation of tourists to share travel experiences through Instagram social media at Padang-Padang beach in general is at good level. 2) based on the analysis of factors obtained the results that there are five motivational factors that motivate tourists to share travel experience through Instagram social media at Padang-Padang beach with the loading value factor of 32,154%. The results of this study can be suggested to the organizer to provide local tour guide who can inform more about Padang-Padang beach to tourists.